Strategi Gastrodiplomasi Indonesia Melalui Program Indonesia Spice Up The World Untuk Meningkatkan Nation Branding Indonesia Di Australia Pada Tahun 2022 - Situmorang, Devina; Lubis, Flori Mardiani; Hakiem, Fadhlan Nur (Peneliti.net, 2024)
Indonesia has made efforts to maximize gastrodiplomacy to international countries, one of which is Australia. Currently, the gastrodiplomacy program that Indonesia is running from 2020 is the implementation of the Indonesia Spice Up The World program. The background of this research is how Indonesia's gastrodiplomacy strategy in improving nation branding in Australia? The method for this research uses descriptive research with a qualitative approach. The results of this study show that the State of Indonesia has implemented various strategies which contain elements of the nation branding dimension. However, the implementation has not been optimal. It is recommended that there be further research on how to update other strategies of various parties ranging from the government, diaspora, and related parties in improving Indonesia's nation branding in Australia during the implementation of the Indonesia Spice Up The World program until 2024.